2021
DOI: 10.35371/aoem.2021.33.e20
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to depressive symptoms in Korean self-employed workers

Abstract: Background We examined factors related to depressive symptoms in Korean self-employed workers. Methods This secondary analysis examined data of 14,454 self-employed individuals from the fifth Korean Working Conditions Survey (2017). Multiple logistic regression analysis was used to assess the relationship of depressive symptoms with different variables. Results Self-employed workers who had a good work-life balance, a good subjective health, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
(35 reference statements)
1
1
0
Order By: Relevance
“…This result is unlike that of a systematic review from Australia (Yazd et al, 2019), which showed the most mentioned impacts on farmers' mental health as pesticide disclosure, financial hardship and physical injuries. However, the present finding is similar to that of a Korean study (Kim et al, 2021), which found that the majority of farmers were relatively able to find work–life balance, had good health opinions and were less likely to report depressive symptoms (4.8%). The reason for differences might be due to the farming variation among different countries, although we used a reliable and valid screening tool to explore subjective feelings in recent weeks, such as trouble sleeping or feeling low.…”
Section: Discussionsupporting
confidence: 91%
“…This result is unlike that of a systematic review from Australia (Yazd et al, 2019), which showed the most mentioned impacts on farmers' mental health as pesticide disclosure, financial hardship and physical injuries. However, the present finding is similar to that of a Korean study (Kim et al, 2021), which found that the majority of farmers were relatively able to find work–life balance, had good health opinions and were less likely to report depressive symptoms (4.8%). The reason for differences might be due to the farming variation among different countries, although we used a reliable and valid screening tool to explore subjective feelings in recent weeks, such as trouble sleeping or feeling low.…”
Section: Discussionsupporting
confidence: 91%
“… 1 2 These occupational stressors increase the risks of depression, sleep disorder, fatigue, and metabolic syndrome. 1 2 3 4 5 6 Long working hours are also associated with smoking, alcohol consumption, and lack of exercise. 7 Lack of sleep, fatigue, burnout, and unhealthy lifestyle of residents increase the risk of occupational injury at the workplace, which is directly related to patient safety.…”
Section: Introductionmentioning
confidence: 99%